SUBSTANTIATION OF PHARMACEUTICAL COMPETENCIES IN THE SYSTEM OF SPECIALIZED PHARMACEUTICAL CARE FOR OCCUPATIONAL DISEASES - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Черных, Наталья Степановна (Medicine in Kuzbass, 2024)
One of the priority and relevant directions of modern pharmaceutical science is the organization of the prevention of occupational diseases in the system of specialized pharmaceutical care for employees of the coal industry. In modern conditions, the preservation of the professional health of the able-bodied population of the country, as the economic basis of society, is the most important medical and social task. The analysis of domestic and foreign literature on the issues of professional interaction between a doctor and a pharmacist is given. The data of Rospotrebnadzor are presented, where occupational diseases are still one of the most common diseases. It is shown that the number of people employed in various sectors of the Russian economy - the main strategic potential of the national security of the state - is 72.1 million people in 2022, according to Rosstat, and the proportion of people employed in jobs with harmful and (or) dangerous working conditions in 2021 is 36.4%. Modern approaches to specialized pharmaceutical care for occupational diseases are considered – ensuring the proper quality of pharmacotherapy for a specific patient with a specific disease. It is shown that the constant interaction of a pharmaceutical worker with a patient and his doctor during pharmacotherapy of a particular disease in order to improve the professional competencies of a doctor and pharmacist is of particular importance in the training of pharmaceutical workers in the specialty "Clinical Pharmacy" in providing specialized medical care to patients with occupational diseases.